2020
DOI: 10.3390/su12083154
|View full text |Cite
|
Sign up to set email alerts
|

Roller Compacted Concrete with Recycled Concrete Aggregate for Paving Bases

Abstract: This research aimed to investigate the mechanical and physical properties of Roller Compacted Concrete (RCC) used with Recycled Concrete Aggregate (RCA) as a replacement for natural coarse aggregate. The maximum dry density method was adopted to prepare RCC mixtures with 200 kg/m³ of cement content and coarse natural aggregates in the concrete mixture. Four RCC mixtures were produced from different RCA incorporation ratios (0%, 5%, 15%, and 30%). The compaction test, compressive strength, splitting tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
(93 reference statements)
0
8
1
Order By: Relevance
“…It can be revealed that dense gradation exhibits lower porosity than gap gradation. Such finding does not match with the results reported by Fardin and Santos, [3]. It can be observed that dense gradation exhibits higher intercept value of 57.3 % than that of gap gradation.…”
Section: Porositycontrasting
confidence: 85%
See 1 more Smart Citation
“…It can be revealed that dense gradation exhibits lower porosity than gap gradation. Such finding does not match with the results reported by Fardin and Santos, [3]. It can be observed that dense gradation exhibits higher intercept value of 57.3 % than that of gap gradation.…”
Section: Porositycontrasting
confidence: 85%
“…However, no meaningful correlation was found between the dry density and capillary absorption coefficient. Fardin and Santos, [3] implemented the maximum dry density method to prepare roller compacted concrete mixtures with 200 kg/m3 of cement content. Four mixtures were produced with recycled coarse aggregates ratios (0, 5, 15, and 30) %.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of low-density porous adhered mortar (AM) around RCA could significantly affect the compactness, and thus, the aggregate interlocking capacity of RCCP; the compactness is usually determined by maximum dry density (MDD) and Vebe density. Based on the available literature, it is confirmed that the density of these hybrid mixtures could be lower than conventional RCCP in the range of 2.2% to 4.7% because of AM ( 7 , 13 , 14 ). Also, the water demand for these mixtures could be 8.3% to 35% higher than conventional mixtures for coarse RCA inclusion ( 7 , 13 , 14 ).…”
mentioning
confidence: 83%
“…Repurposing structural components to produce "new" items is difficult. Therefore, researchers are exploring approaches to repurpose recycled concrete including as construction materials e.g., [33][34][35], and geotechnical applications e.g., [36][37][38]. However, consumers may be hesitant to use these materials and applications because the minimum specifications have not been met.…”
Section: Low Demand For Recycled Concretementioning
confidence: 99%